A Rare Case of Extensive Lichen Striatus - S. Marahatta; D.K. Khadka; M. Agarawal (Nepal Journal of Dermatology, Venereology & Leprology)
Lichen striatus is a rare dermatitis characterized by lichenoid papules arranged in a linear band along the Blaschko’s line. Extremities are commonly affected sites. Sometimes, abdomen, buttocks and thighs may also be involved in a single extensive lesion. But, multiple lesions involving many Blaschko’s lines are rare with only few publications till now. Hence, we are reporting a case of 14-year-old male presented with lichen striatus over left upper and lower extremities as well as left side of trunk.